Analysis of The Influence of Hedonic Motivation, Digital Devices Ease of Use Perception, Benefits of Digital Technology and Digital Promotion on Intention to Use of Digital Wallets Consumers - Sudirjo, Frans; Mustafa, Fahrina; Diah Astuti, Enny; Tawil, Muhamad Risal; Budiwidjojo Putra, Alfa Santoso (SEULANGA SYSTEM PUBLISHER, 2023)
The purpose of this study is to ascertain whether consumer intention to use and behavior with regard to digital wallets is influenced by factors such as sales promotions, habits, hedonic motivation, perceived benefits, and convenience. The demographic included in this study consists of actual people who use digital wallets in Indonesia. Purposive sampling combined with non-probability sampling was the sample strategy employed. The sample for this study included 200 users of digital wallets. In this study, a field survey with a questionnaire instrument was used as the data gathering method. Path analysis using SPSS AMOS is the data analysis technique employed in this study. The findings of the study led to the following deductions: The benefits that users of digital wallets believe to be obtained are influenced by their perceived convenience. Perceived ease of use has no bearing on users' intention to use digital wallets. Perceived utility has no bearing on a person's inclination to utilize a digital wallet. Perceived benefits have an impact on consumers' usage behavior while using digital wallets. The intention to utilize a digital wallet is influenced by hedonic incentive. The intention to utilize digital wallets is influenced by one's behaviors. The usage patterns of users of digital wallets are influenced by habit. Sales promotions have little effect on how users of digital wallets use their devices. Users' usage behavior of digital wallets is influenced by their intention to use one.